Portrait of a Priestess : Women and Ritual in Ancient Greece - Connelly, Joan Breton, 1954- (Book collections on Project MUSE., 2007)
Archaeologist Connelly gives us the first comprehensive cultural history of priestesses in the ancient Greek world. Connelly presents the fullest picture yet of how priestesses lived and worked, from the most famous and sacred of them--the Delphic Oracle and the priestess of Athena Polias--to basket bearers and handmaidens. Along the way, she challenges long-held beliefs to show that priestesses played far more significant public roles in ancient Greece than previously acknowledged. Connelly examines archaeological evidence in the broader context of literary sources, inscriptions, sculpture, and vase painting. The picture that emerges reveals that women in religious office were not as secluded and marginalized as we have thought--that religious office was one arena in ancient Greece where women enjoyed privileges and authority comparable to that of men. Connelly concludes by examining women's roles in early Christianity, taking on the larger issue of the exclusion of women from the Christian priesthood.--From publisher description.